Analisis titik kritis kehalalan soto Sokaraja - Hety Handayani Hidayat; Nur Wijayanti; Sawitania Christiany Dwi Utami Boru Situmorang (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Food producers should guarantee the halalness of their products for consumers, especially Muslim consumers. This does not only apply to packaged food but also ready-to-eat food such as soup. Therefore, this study aims to map the critical points of halal in the production process of Soto Sokaraja products, both in terms of ingredients, production process, presentation, and the facilities used. Data collection was carried out by interviewing the owner and direct observation. Then adjustments were made to the rules and guidelines related to halal, which refer to the Halal Assurance System (SJH). The method used to determine the critical halal point is the Halal Critical Point (HCP) decision tree diagram from LPPOM MUI. The results showed that the essential topics for the ingredients were beef/chicken/tripe, ketupat, crackers, palm sugar, and packaging materials (styrofoam). The critical points of the production process lie in the preparation process, making the soto and peanut sauce seasonings and the soto compounding process. As for the facility criteria, the critical point for halal is the cleanliness of the equipment from unclean contamination. In the future, there will be socialization and education from BPJPH, related agencies and the Halal Center in the Banyumas area, assembling the Halal Assurance System for Soto Sokaraja business actors